Strategi Pengelolaan Estetika Visual Media Ajar Ilmu Tauhid Berbasis Canva - Sheila Mafaizah; Irawan Irawan (Mathematics Education Study Program, 2025)
This study aims to analyze the visual aesthetics management strategies for Ilmu Tauhid (Theology) teaching media based on Canva, as implemented by first-semester PAI (Islamic Religious Education) students at UIN Sunan Gunung Djati Bandung. This qualitative research utilizes Roland Barthes' semiotic analysis to uncover the denotation, connotation, and myth contained in ten digital teaching media, with three products selected as a purposive sample. Data was collected through document analysis of student presentation files and in-depth observation of visual elements, then analyzed using Barthes' semiotic stages. The results conclude that students have implemented visual aesthetics management strategies maximally and with theological awareness, aligning with Seyyed Hossein Nasr's principles of Islamic Aesthetics: simplicity of form, regularity of pattern, and oneness (tauhid). Barthes' analysis reveals that students' visual decisions successfully move beyond mere visual description (denotation) to uncover hidden meanings (connotation) and theological ideology (myth) embedded in the design. Overall, students apply five management strategies, which are a blend of design principles, Tauhid values, and media learning management practices. The novelty of this research lies in the use of Roland Barthes' Semiotic Analysis to address the visual aesthetics management strategies of Canva-based teaching media.